Asia's largest urban slum-Dharavi: A global model for management of COVID-19 - Kaushal, Jyotsna (Cities, 2021)
The Dharavi sector of Mumbai, India is constituted as one of the biggest slums of Asia and the world's most populated areas. The COVID-19 outburst is at its peak in May and curve gets flattened within next two months. This article focuses on factors responsible for transmission, prevention and in controlling the COVID-19 spread in Dharavi. The COVID-19 data was interpreted in terms of Case Recovery Rate (CRR) and Case Fatality Rate (CFR) for total and closed both. The CFR per closed reached 10.12% nearly to per total 9.82% in Dharavi on 31st July 2020. The CRR per total cases in Dharavi and Mumbai is 87.16 & 76.18% and per closed cases is 89.87 & 93.20% respectively in comparison to the CFR. The calculated CFR and CRR for both Dharavi and Mumbai suggest that the COVID-19 recovery rate is more than the fatality rate. The Dharavi people serve as an important role in controlling the pandemic by adopting 4-T model tracing, tracking, testing, and treating strategy. This article is beneficial for government policy makers and private agencies in controlling the COVID-19 pandemic in densely populated areas and also for nations with high fatality rate.